2005
DOI: 10.1080/14620316.2005.11511996
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of epicuticular wax aggregates during fruit development in apple (Malus domesticaBorkh.)

Abstract: To cite this article: Eric Curry (2005) Ultrastructure of epicuticular wax aggregates during fruit development in apple (Malus domestica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
2
20
0
4
Order By: Relevance
“…They occurred more abundantly after storage, when vertically and obliquely oriented wax platelets merged and filled the microcracks. The shapes of epicuticular wax crystals found in the present study are similar to those reported previously (Glenn et al, 1990;Roy et al, 1994;Koch et al, 2004;Curry, 2005). Lurie et al (1996) and Curry (2001) suggested that a tear-and-repair mechanism operates in apple fruits, thanks to which microcracks on the apple surface are gradually cicatrized and covered by newly crystallized wax platelets produced during storage.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…They occurred more abundantly after storage, when vertically and obliquely oriented wax platelets merged and filled the microcracks. The shapes of epicuticular wax crystals found in the present study are similar to those reported previously (Glenn et al, 1990;Roy et al, 1994;Koch et al, 2004;Curry, 2005). Lurie et al (1996) and Curry (2001) suggested that a tear-and-repair mechanism operates in apple fruits, thanks to which microcracks on the apple surface are gradually cicatrized and covered by newly crystallized wax platelets produced during storage.…”
Section: Discussionsupporting
confidence: 81%
“…Riederer and Schreiber (1995) and Knoche et al (2000) suggest that the amount of wax but not cuticle thickness is correlated with the quantity of water transpired from fruits, although, as demonstrated by Veraverbake et al (2003a), the diffusion coefficient of cutin and cuticle is 4-fold higher than that of wax. Changes in the amount of wax during growth and storage have been demonstrated in many apple varieties (Morice and Shortland, 1973;Belding et al, 1998Belding et al, , 2000Veraverbake et al, 2001;Curry, 2005; Tab. 1) and in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2 A and E). Under favorable environmental conditions, this process occurs gradually, beginning the repair of microcracks through the parallel deposition of wax platelets before the complete disruption and exposure of underlying epidermal cells in a procedure, known as "tear and repair" (Curry 2005). This pattern was observed in both the cultivars (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…The elongation process of wax microtubules, aggregation, crystallization and polymerization occur simultaneously during the fruit growth, causing the deposit of wax platelets on the cuticle and on the microcracks formed in it, a procedure known as "Tear and Repair" (Curry 2009). Wax production continues during the storage (Belding et al 1998), until the origin cells become biochemically inhibited, necrotic or without substrate (Curry 2005). The fruits of different apple cultivars vary in terms of epicuticular waxes morphology, quantity and chemical composition during development, as well as during the storage and subsequent life (Veraverbeke et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…8 -10 Differences in epicuticular wax morphology, quantity and chemical composition among apple cultivars have been reported during fruit development, cold storage and subsequent shelf life. 11,12 Others have shown physicochemical differences in apple epicuticular wax due to environmental stresses such as rain acidity, temperature and radiation. 13 -16 Under certain conditions, some apple cultivars such as 'Granny Smith' and 'Royal Gala' may become greasy during ripening, both on the tree and during cold storage, owing to changes in production of surface lipids.…”
Section: Introductionmentioning
confidence: 99%